Behold the man, the hero, the heretic. - Chia Chong Hui, Steven. (2011)
Why do we read superhero comics? Superhero narratives have developed into a special genre which incorporates science fiction, magical fantasy, and even theology to provide an entertaining and enriching read. More than that however, many superhero feats have gone on to be proven by science as remarkably intuitive and insightful of past, present and future developments in technology.